Bitter taste receptors along the gastrointestinal tract: comparison between humans and rodents - Descamps-Solà, Maria; Vilalta, Adrià; Jalsevac, Florijan; Blay, M. Teresa; Rodríguez-Gallego, Esther; Pinent, Montserrat; Beltrán-Debón, Raúl; Terra, Ximena; Ardévol, Anna (Frontiers in Nutrition, 2023)
For decades bitter taste receptors (TAS2R) were thought to be located only in the mouth and to serve as sensors for nutrients and harmful substances. However, in recent years Tas2r have also been reported in extraoral tissues such as the skin, the lungs, and the intestine, where their function is still uncertain. To better understand the physiological role of these receptors, in this paper we focused on the intestine, an organ in which their activation may be similar to the receptors found in the mouth. We compare the relative presence of these receptors along the gastrointestinal tract in three main species of biomedical research (mice, rats and humans) using sequence homology. Current data from studies of rodents are scarce and while more data are available in humans, they are still deficient. Our results indicate, unexpectedly, that the reported expression profiles do not always coincide between species even if the receptors are orthologs. This may be due not only to evolutionary divergence of the species but also to their adaptation to different dietary patterns. Further studies are needed in order to develop an integrated vision of these receptors and their physiological functionality along the gastrointestinal tract.